IMPACT OF HELLO WORDS ‘HELLOTALK APP’ ON STUDENTS’ ENGLISH VOCABULARY AT JUNIOR HIGH SCHOOL - Asoka, Niken Puspa; Ginting, Pirman; Lubis, Bambang Nur Alamsyah (Universitas Muhammadiyah Palembang, 2024)
Vocabulary serves as the foundation for increasing language skills for language learners. This research aimed to find out the significant impact of the hello words feature in the Hellotalk app on increasing the English vocabulary of 16 students in grade 8. The research utilized a pre-experimental method with a one-group pre-test and post-test design. Data were collected through a multiple-choice vocabulary test. The research process included a pre-test, treatments, and a post-test. Data analysis was using SPSS 27.01 with descriptive statistics, normality tests, homogeneity tests, and paired sample t-tests. The results revealed that the hello words feature in the Hellotalk app significantly increased students' English vocabulary, with an average pre-test score of 58.3313 and a post-test score of 82.5006. At a significance level of ? = 0.05, the paired sample t-test revealed a significance value (2-tailed) of < 0.001, which is smaller than 0.05. Therefore, the null hypothesis (H?) was rejected, and the alternative hypothesis (H?) was accepted.